Association of Microsatellites D4S2912, D4S230 and D4S3001 (4P15.1) to type 2 diabetes in peruvian population - Paredes Anaya, Mónica (2015)
Objective: To determine the association of microsatellite markers D4S2912, D4S230 and D4S3001 with diabetes type 2 (DM2) in the Peruvian population. Material and Methods: We analyzed the microsatellite markers D4S2912, D4S230 and D4S3001 in 99 diabetics and 120 healthy individuals to D4S2912, D4S230 and 129 to 133 for D0453001 as controls from Lima. We processed the 0NA extracted from blood intravenously, amplified by the technique of polymerase chain reaction (PCR) for the three markers in the region 4p15.1. Finally, we analyzed the polymorphisms of the markers and determined the genetic homogeneity of the population through proof of Hardy-Weinberg (HW), and continued in the study of association of 0M2 in patients versus controls. Results: In D4S2912 and D4S3001 there was absence of an allele in the control group when compared with the diabetic population. When performing association analysis using conditional logistic regression model and the Monte Carlo permutation test, they showed an association between D4S3001 and Peruvian population with DM2. Conclusion: This research shows the microsatellite D4S3001, located on chromosome 4p15.1 region as a marker associated with DM2 in the Peruvian population and is located in a chromosomal region that contain a gene(s) which would play a role in the etiology DM2.